THE TRANSFORMATION OF TRADITIONAL ISLAMIC BOARDING SCHOOLS INTO INTEGRATED PESANTREN: CURRICULUM, GOVERNANCE, AND TECHNOLOGICAL ADAPTATION - Taqiyuddin Taqiyuddin; Iwan Iwan; Ade Aspandi (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
Pesantren, as the oldest Islamic educational institutions in Indonesia, face modernization challenges that require systemic transformation while preserving their traditional identity. This study analyzes the transformation of Salafiyah pesantren into integrated pesantren at KHAS Kempek Cirebon, focusing on curriculum integration, institutional governance, and technological adaptation. Using a qualitative case study approach, data were collected through interviews, participant observation, and documentation involving kiai, ustadz, administrators, and santri. The findings show that the transformation is adaptive and integrative. Traditional learning methods such as sorogan, bandongan, and wetonan are maintained while supported by structured management systems, formal education integration, and digital technology utilization. National education standards are also adopted without eliminating Salafiyah values as the pesantren’s primary foundation. The transformation expands the role of pesantren from centers of Islamic learning into adaptive and competitive educational institutions. This study contributes a multidimensional perspective showing that curriculum, governance, and technology function as interconnected elements in sustaining pesantren transformation within contemporary Islamic education.